PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 1 SD SUPRIYADI SEMARANG - Ahmad Rohman Yusuf; Fenny Roshayanti; Ervina Eka Subekti (STKIP Subang, 2023)
This research was motivated by the low learning outcomes of students, especially in class 1A SD Supriyadi Semarang in learning Mathematics CHAPTER 5 Time measurement. The low learning outcomes of students are due to the inappropriate use of the Learning Model in Class 1A Students of SD Supriyadi Semarang, in delivering the material, the teacher does not apply the contextual teaching and learning model. The purpose of carrying out this research is to improve the learning outcomes of class 1A students at SD Supriyadi Semarang. The study used a class action research method (CAR), which consisted of two cycles. The results of the study showed that there was an increase in students from cycle one to cycle two. This change occurred due to the action of changing the contextual learning model in learning carried out in mathematics subject CHAPTER 5 Time Measurement. In cycle 1, there were 15 students out of 28 who scored above the Learning Objective Completeness Criteria (KKTP) with a percentage of 53.6%. In the second cycle of students who have scores above the Learning Objectives Completeness Criteria (KKTP), there are 25 students out of 28 with a percentage of 89.3%. This shows that the research target in class 1A SD Supriyadi Semarang has been achieved in cycle 2 with a percentage of completeness above the average.